β-Cell Calcium-Independent Group VIA Phospholipase A(2) (iPLA(2)β): Tracking iPLA(2)β Movements in Response to Stimulation With Insulin Secretagogues in INS-1 Cells - Bao, Shunzhong (2004)
Evidence that group VIA cytosolic calcium-independent phospholipase A(2) (iPLA(2)β) participates in β-cell signal transduction includes the observations that inhibition of iPLA(2)β with the bromoenol lactone suicide substrate suppresses glucose-stimulated insulin secretion and that overexpression of iPLA(2)β amplifies insulin secretory responses in INS-1 insulinoma cells. Immunofluorescence analyses also reveal that iPLA(2)β accumulates in the perinuclear region of INS-1 cells stimulated with glucose and forskolin. To characterize this phenomenon further, iPLA(2)β was expressed as a fusion protein with enhanced green fluorescent protein (EGFP) in INS-1 cells so that movements of iPLA(2)β are reflected by changes in the subcellular distribution of green fluorescence. Stimulation of INS-1 cells overexpressing iPLA(2)β-EGFP induced greater insulin secretion and punctate accumulation of iPLA(2)β-EGFP fluorescence in the perinuclear region. To determine the identity of organelles with which iPLA(2)β might associate, colocalization of green fluorescence with fluorophores associated with specific trackers targeted to different subcellular organelles was examined. Such analyses reveal association of iPLA(2)β-EGFP fluorescence with the ER and Golgi compartments. Arachidonate-containing plasmenylethanolamine phospholipid species are abundant in β-cell endoplasmic reticulum (ER) and are excellent substrates for iPLA(2)β. Arachidonic acid produced by iPLA(2)β-catalyzed hydrolysis of their substrates induces release of Ca(2+) from ER stores—an event thought to participate in glucose-stimulated insulin secretion.